A relative murder - Deveraux, Jude (Deveraux, Jude. Medlar mystery, 2022)
"Bestselling novelist Sara Medlar is skilled at sharing stories about other people, but she hoped the truth about her own family would never surface. Her home in Lachlan, Florida, is her refuge and she loves having her niece Kate and dear friend Jack Wyatt together under her roof. The Medlar Three, as they are known around town, have sworn off getting involved in any more murder investigations. When the sheriff unexpectedly leaves on vacation, Jack is surprised to find himself appointed as deputy. So when Kate stumbles upon a dead body while visiting a friend, the Medlar Three are back in the sleuthing game. Kate also has a charming new real estate client with a mysterious past. He seems to be followed by trouble and that makes Sara and Jack uneasy. It doesn't take long to discover that the murder and the new man in town are somehow related--the question is how. When the stranger's true identity is revealed, Sara realizes her carefully crafted story is about to unravel and she fears she'll lose Kate and Jack forever. But she desperately hopes that love and honesty will win out over years of lies and deceit. And besides, family is family--even if you sometimes want to kill them." --provided by Goodreads.